Sustainable food consumption and Sustainable Development Goal 12: Conceptual challenges for monitoring and implementation - Kristina Mensah; Christine Wieck; Bettina Rudloff (Sustainable Development, 2023)
In recent years, policy initiatives have been developed to promote sustainability. Although sustainable food production is an integral part of many national agricultural policies, this is not the case for sustainable food consumption. This article systematically reviews key elements of sustainable food consumption and evaluates how they align with existing policy indicators, specifically SDG 12, within the context of the agricultural policy of the European Union. Through a cross-referencing approach, this article identifies gaps and possible improvements in policy indicator frameworks to better capture elements of sustainable food consumption. We find that SDG 12 targets are not suitable to assess progress to sustainable food consumption. While targets are closely linked to environmental and economic issues, they are insufficient to monitor sustainable food consumption. Our findings suggest the necessity for enhanced or modified policy indicators that encompass the key elements of sustainable food consumption as well as a comprehensive definition of the latter to effectively design and evaluate polices on this matter.
Keywords: 330; cross-referencing; European Union; food; indicator; monitoring; sustainability; sustainable diets